Novel STAMBP mutation and additional findings in an Arabic family. (18th February 2015) - Faqeih, Eissa A.; Bastaki, Laila; Rosti, Rasim Ozgur; Spencer, Emily G.; Zada, AbdulAli P.; Saleh, Mohammad A. M.; Um, Kyongmi; Gleeson, Joseph G.
Abstract : Microcephaly‐capillary malformation syndrome (MIC‐CAP syndrome) is a newly recognized autosomal recessive congenital neurocutaneous central nervous system disorder characterized by severe microcephaly, early‐onset seizures, profound psychomotor disability, and multiple cutaneous capillary lesions. In addition, affected patients have variable dysmorphic facial features and hypoplastic distal phalanges. It is distinctively caused by mutations in a newly characterized gene, STAMBP, encoding the deubiquitinating (DUB) isopeptidase that has a key role in cell surface receptor‐mediated endocytosis and sorting. Herein, we describe an Arab family of two siblings with classic features of MIC‐CAP syndrome that harbor a novel predicted splice mutation in STAMBP, which additionally display previously unreported findings of congenital hypothyroidism and alopecia areata. © 2015 Wiley Periodicals, Inc.